Clostridioides difficile Biology: Sporulation, Germination, and Corresponding Therapies for C. difficile Infection - Zhu, Duolong; Sorg, Joseph A.; Sun, Xingmin (Frontiers in Cellular and Infection Microbiology, 2018)
Clostridioides difficile is a Gram-positive, spore-forming, toxin-producing anaerobe, and an important nosocomial pathogen. Due to the strictly anaerobic nature of the vegetative form, spores are the main morphotype of infection and transmission of the disease. Spore formation and their subsequent germination play critical roles in C. difficile infection (CDI) progress. Under suitable conditions, C. difficile spores will germinate and outgrow to produce the pathogenic vegetative form. During CDI, C. difficile produces toxins (TcdA and TcdB) that are required to initiate the disease. Meanwhile, it also produces spores that are responsible for the persistence and recurrence of C. difficile in patients. Recent studies have shed light on the regulatory mechanisms of C. difficile sporulation and germination. This review is to summarize recent advances on the regulation of sporulation/germination in C. difficile and the corresponding therapeutic strategies that are aimed at these important processes.